IMPLEMENTASI MANAJEMEN RESIKO PADA SISTEM ASURANSI JIWA SYARIAH DI PT. PRUDENTIAL LIFE ASSURANCE CABANG MADURA - Toyyibah Toyyibah; Erie Hariyanto (Institut Agama Islam Negeri Madura, 2015)
This article discusses about risk management in the company of shari’ah life insurance. Shari’ah insurance is generally not much different from conventional insurance. Between insurances in the perspective of Islamic sharia’h with conventional insurance have the similarity, namely the insurance company is only as a facilitator of structural relationships between participants purveyor of premium (insurer) with receiving member of payment of claims (insured), will be described how to overcome the risks problems faced the company and if possible minimized the risk, in order to be created efficiency and effectiveness will finally help and facilitate the achievement of company objectives. This may be as operational risks as failed to pay, the legal risk, and reputational risk but it is also a moral hazard, also frequently found obstacles faced by the company sourced from externals and internals of company.